Public value creation mechanisms in the context of public service logic : an integrated conceptual framework - Virtanen, Petri; Jalonen, Harri (Taylor & Francis, 2023)
This conceptual paper maintains that mainstream public management theories have failed to incorporate public services as a fundamental part of the public administration system. That failure does a disservice to the potential of public services to address societal betterment through the creation of public value, which can strengthen democracy. This paper presents an integrated conceptual framework to help make sense of the public value creation flows in the context of politics (encompassing public policy and public service goal attainment) and public service outcomes. We suggest there are four flows creating public value.
Keywords: Public service logic; public value; public leadership; co-creation; value-in-use; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|